MAINSTREAMING DISTANCE LEARNING INTO THE COMMUNITY COLLEGE - Thor, Linda M.; Scarafiotti, Carol (Online Learning, 2004)
Rio Salado, one of the Maricopa Community Colleges in the Phoenix metropolitan area, has not only carved a market niche as a leading distance learning provider for working adults, but has experienced double-digit growth increases as high as 40 percent annually in its online enrollments. With unduplicated headcount exceeding 21,000 distance learning students last year, the majority of them enrolled in webbased courses, this college without a campus has been recognized as a national model for online teaching and learning. This article details how Rio Salado has mainstreamed distance learning throughout the entire college.